Impact of End-Tethered Polyhedral Nanoparticles on the Mobility of Poly(dimethylsiloxane) - Cosgrove, Terence (Langmuir : the ACS journal of surfaces and colloids, 2015)
A series of dumbbell-shaped nanocomposite materials of poly(dimethylsiloxanes) (PDMSs) and polyhedral oligomeric silsesquioxanes (POSSs) were synthesized through hydrosilylation reactions of allyl- and vinyl-POSS and hydride-terminated PDMS. The chemical structures of the dumbbell-shaped materials, so-called POSS-PDMS-POSS triblocks, were characterized by (1)H NMR and FT-IR spectroscopy. The molecular weights of the triblock polymers were determined by gel permeation chromatography (GPC). Their size was analyzed by small-angle neutron scattering (SANS) and pulsed-field gradient stimulated echo (PFG STE) NMR experiments. The impact of POSS on the molecular mobility of the PDMS middle chain was observed by using (1)H spin-spin (T2) relaxation NMR. In contrast to the PDMS melts, the triblocks showed an increase in mobility with increasing molecular weight over the range studied due to the reduced relative concentration of constraints imposed by the end-tethered nanoparticles. The triblock systems were used to compare the impact of tethered nanoparticles on the mobility of the linear component compared to the mobility of the polymer in conventional blended nanocomposites. The tethered nanoparticles were found to provide more reinforcement than physically dispersed particles especially at high molecular weights (low particle concentration). The physical blends showed an apparent percolation threshold behavior